PENDAMPINGAN PENULISAN ARTIKEL ILMIAH MENUJU JURNAL BEREPUTASI NASIONAL BAGI MAHASISWA - Muh. Jelani Al Pansori; Baiq Rismarini Nursaly; Herman Wijaya; Moh. Irfan (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
This Community Service Program (PkM) aimed to enhance the ability of final-year students of the Faculty of Language, Arts, and Humanities, Hamzanwadi University, in writing scientific articles eligible for publication in nationally accredited journals. The main problems encountered by students included low reading interest, lack of self-confidence, limited mastery of research theory and methodology, and insufficient academic writing skills, which hindered them from transforming their theses into publishable articles. The implementation was designed in three stages. First, the preparation stage involved participant selection, needs assessment, and scheduling. Second, the technical training stage was conducted through workshops and writing clinics, covering article structure, academic language use, abstract and conclusion writing, reference management with Mendeley, and manuscript editing using Grammarly. Participants were also introduced to publication ethics, particularly issues of plagiarism. Third, the intensive mentoring stage provided personal guidance from lecturers and senior student assistants to revise and finalize manuscripts for submission to national journals. The results indicated that intensive mentoring was effective in improving students’ academic writing skills. Students gained a better understanding of article structure, enhanced their ability to use academic language, mastered citation techniques, and developed skills in manuscript editing. Thus, this program not only addressed students’ difficulties in article writing but also produced tangible outputs in the form of publishable articles and a training module that can be utilized sustainably.